The need for international search and rescue (SAR) teams during an earthquake: Nepal case study. Issue 7 (2nd October 2016) - Shenhar, Gili; Adamcheck, Rebecca; Hopmeier, Michael
ABSTRACT: On 25 April 2015, a 7.8 magnitude earthquake struck Nepal, causing huge damage. Many countries and international organisations such as the United Nations started monitoring the situation and offered support to the Nepali government. This article raises points that must be examined by decision-makers before implementing delegations; these include cost effectiveness, whether it improves morale and resilience, international relations, and experience, and promotes good relationships between the two countries, and assisting their own citizens who were affected by the disaster.